Performance evaluation of two CAC algorithms in ATM networks - Chaves, Niudomar Siqueira de Araújo (2000)
This paper presents a performance study of two CAC (Connection Admission Control) algorithms. Both algorithms are based on effective bandwidth concept. The results were obtained through simulation. The analysis showed that the required QoS is achieved by the two algorithms, however, they overestimate the necessary bandwidth resulting in lower network resource utilization